Temperature-dependent study of gelling biopolymers using infrared spectroscopy - Bakhai, Bijol (2022)
This Thesis is centred around understanding conformational changes that occur within biopolymers which have major implications in food industry. Monitoring the continuous conformational changes of biopolymers subjected to temperature changes presents a challenge. Infrared spectroscopy is a powerful spectroscopic technique that can measure structural changes quantitatively. This Thesis focuses on probing the temperature-variable changes of gelling biopolymers, using Fourier transform infrared (FTIR) spectrometer coupled with a modified attenuated total reflectance (ATR) accessory, to determine the conformation and dynamics of the system. The modified system allowed for continuous collection of spectral data (stable to 0.01 °C), with precise control and variation of the sample over a temperature range of -15 °C to +80 °C.